Amperometric cholesterol biosensor based on cholesterol oxidase and Pt-Au/ MWNTs modified glassy carbon electrode. (2022) - Haritha, V.S.; Kumar, S.R. Sarath; Rakhi, R.B.
Abstract: The present work investigates the fabrication and performance studies of nanoscale metal cluster loaded Multi-Walled Carbon Nanotubes (MWNTs) based amperometric cholesterol biosensors. By a simple chemical reduction method Pt/ MWNTs, Au/MWNTs, and Pt-Au/MWNTs nanocomposites are prepared. Metal-decorated MWNTs are characterized by using X-ray diffraction analysis, scanning electron microscopy, and transmission electron microscopy (TEM). Amperometric biosensors are fabricated by depositing cholesterol oxidase (COx) enzyme on nanocrystalline metal/MWNTs modified GCE. Performance studies of these fabricated biosensors are conducted by using cyclic voltammetry and amperometry. The fabricated Au/MWNT based biosensor is best suited for the determination of cholesterol with a response time of 15 s, linear range from 2 µM to 1.4 mM, and limit of detection (S/N = 3) of 0.5 µM.